Ink material selection and optical design considerations in DLP 3D printing. (February 2023) - Goodarzi Hosseinabadi, Hossein; Nieto, Daniel; Yousefinejad, Ali; Fattel, Hoda; Ionov, Leonid; Miri, Amir K.
Highlights: This review focuses on ink selection and design parameters for DLP-printing of soft structures. DLP strategies that improve the level of automation are summarized to overcome DLP limitations. The role of the ink chemistry and monomer molecular structure in performance of DLP are discussed. The kinetics of light absorption and photopolymerization reaction in DLP are explained. A roadmap is provided to select proper sets of DLP parameters and ink formulation for desired demand. Abstract: Digital light processing (DLP) 3D printing has become a powerful manufacturing tool for the fast fabrication of complex functional structures. The rapid progress in DLP 3D printing has been linked to research on optical design factors and ink selection. This critical review highlights the main challenges in the DLP 3D printing of photopolymerizable inks. The kinetics equations of photopolymerization reaction in a DLP printer are solved, and the dependence of curing depth on the process optical parameters and ink chemical properties are explained. Developments in DLP platform design and ink selection are summarized, and the roles of monomer structure and molecular weight on printing resolution are shown by experimental data. A detailed guideline is presented to help engineers and scientists to select inks and optical parameters for fabricating functional structures for multi-material and 4D printing. Graphical abstract: Image, graphical abstract